Transparent and Superamphiphobic Surfaces from One‐Step Spray Coating of Stringed Silica Nanoparticle/Sol Solutions. (20th February 2014) - Ge, Dengteng; Yang, Lili; Zhang, Youfa; Rahmawan, Yudi; Yang, Shu
<x xml:space="preserve">Abstract</x> Transparent and superamphiphobic coatings that repel both water and low‐surface‐tension oil offer energy and environmental benefits to building windows, solar cell panels, electronic displays, and other optical equipment. Here, we developed a solution consisting of stringed amphiphilic silica nanoparticles (NPs) and an amphiphilic sol, which could be spray coated onto a variety of planar and curved substrates in one step. High transparency, water/oil contact angles greater than 150° and roll‐off angles less than 10° were demonstrated. The stringed NPs formed a fractal‐like nanoporous network, while the sol acted as a surface modifier and binder to enhance the coating robustness against heating (up to 400 °C), water jetting, and sand abrasion.